Sex Identification Based on Tooth Crown Trait Analysis Among the Mongoloid Race - Syifa Ahliya; Bambang Tri Hartomo; Angger Waspodo Dias Adrianto; Agoeng Tjahajani Sarwono; Elza Ibrahim Auerkari (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine whether anterior and posterior tooth crown traits exhibit sexual dimorphism and identify traits characteristic to the Mongoloid race, especially among the Indonesian population. Material and Methods: This study cross-sectional study analyzed 108 dental casts from 36 males and 72 females. The traits analyzed included winging, shoveling, double shoveling, canine mesial ridge, canine distal accessory ridge, hypocone, metaconule, Carabelli's cusp, protostylid, metaconulid, enteconulid, and hypoconulid. All tooth crown traits were scored based on the ASUDAS scoring system. Descriptive statistics were used to calculate the absolute and relative frequencies. The Chi-square tests was used to determine significant differences in anterior and posterior tooth crown traits between males and females. Level of significance was set at 5%. Results: None of the traits showed sexual dimorphism. Moreover, the most common traits among the Mongoloid race were hypocone (94.4%) and shoveling (86.1%). Conclusion: Although none of the traits exhibited sexual dimorphism, most of them had a higher incidence among females than males. Nonetheless, further research including adequate samples and a similar number of females and males, is needed, especially for population studies.